2003
DOI: 10.1002/masy.200350916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well‐defined poly(p‐benzamide) from chain‐growth polycondensation and its application to block copolymers

Abstract: Poly(p‐benzamide) with a defined molecular weight and a low polydispersity and block copolymers containing this well‐defined aramide was synthesized. Phenyl 4‐(4‐octyloxybenzylamino)benzoate (1b) polymerized at room temperature in the presence of base and phenyl 4‐nitrobenzoate (2a) as an initiator in a chain‐growth polycondensation manner to give well‐defined aromatic polyamides having the 4‐octyloxybenzyl groups as a protecting group on nitrogen in an amide. It was confirmed by a model reaction that deprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Ciferri et al have exploited the strong hydrogen bonding ability of poly(p-benzamide)s (PPBA) in block copolymers formed from PPBA and poly(ethylene glycol) (PEG). [20] Yokozawa et al developed a chain-growth polymerization route to PPBAs [21] and have reported triblock architectures with an outer PEG and an inner PPBA block. [22] Rod-coil block copolymers with well-defined, that is, monodisperse, OPBA as the rigid block have, to the best of our knowledge, not yet been reported.…”
Section: Full Papermentioning
confidence: 99%
“…Ciferri et al have exploited the strong hydrogen bonding ability of poly(p-benzamide)s (PPBA) in block copolymers formed from PPBA and poly(ethylene glycol) (PEG). [20] Yokozawa et al developed a chain-growth polymerization route to PPBAs [21] and have reported triblock architectures with an outer PEG and an inner PPBA block. [22] Rod-coil block copolymers with well-defined, that is, monodisperse, OPBA as the rigid block have, to the best of our knowledge, not yet been reported.…”
Section: Full Papermentioning
confidence: 99%
“…[48] Most of Yokozawa's work [45,47,50,53] was focused on the syntheses of aromatic polyamides. [54,58,[60][61][62]65,66] In numerous experiments phenyl N-alkyl-4-aminobenzoates were used as monomers. The N-substitution served two purposes.…”
Section: Frommentioning
confidence: 99%
“…[50] Diblock copolymers that consist of two differently substituted 4-amino benzoyl units (14 or 15) were prepared by means of phenyl 4-nitrobenzoate as initiator (Equation (45) and (46), Scheme 13). [47,54] Furthermore, star-shaped polyamides having three or four star arms were obtained, when the aromatic phenyl ester 16, 17 or 18 ( Figure 3) were used as electrophilic initiators. [60] Further experiments were conducted with the purpose to prepare homo-and copolyamides of N-substituted meta-aminobenzoic acids.…”
Section: Frommentioning
confidence: 99%
“…The CGC process, like other traditional living polymerization techniques, allows for the synthesis of block copolymers, and more recently, the synthesis of surface-initiated polymer brushes from polymers traditionally prepared using step-growth polymerization. [10,11] Aromatic polyamides are selected by industry for their impressive mechanical and thermal properties and notable chemical resistance. [12] Conventionally, the most famous aromatic polyamides, such as Kevlar © and Nomex © , are synthesized using a step-growth process where an aromatic diamine is reacted with a corresponding aromatic diacid chloride, producing very robust materials, due to the strength and stability of the aromatic backbones and the presence of hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%